Constructivism Theory Of Learning Solutions During The Covid-19 Pandemic In Indonesia - Resti Arifah; Ismail Marzuki (Peneliti.net, 2021)
Constructivism implies that learners are encouraged to construct their own knowledge instead of copying it from an authority, be it a book or a teacher, in realistic situations instead of decontextualised, formal situations such as propagated in traditional textbooks, and together with others instead of on their own. Constructivism's central idea is that human knowledge is constructed, that learners build new knowledge upon the foundation of previous learning. This view of learning sharply contrasts with one in which learning is the passive transmission of information from one individual to another, a view in which reception, not construction, is key. Indonesia was affected by a new epidemic namely the covid-19 virus. Covid-19 has become a pandemic because the number of confirmed cases in Indonesia continues to increase, so Indonesia urgently needs procedures for controlling and preventing the covid-19 pandemic esspesially in education. The method used by the authors is literature review. This paper tries to analyze That the theory of constructivism is a learning solution during the covid-19 pandemic in Indonesia.